Description and Biological Studies of a New Species of Metaphycus Mercet, 1917 (Hymenoptera: Encyrtidae), A Parasitoid of Capulinia linarosae Kondo & Gullan. (July 2019) - Chirinos, Dorys T; Kondo, Takumasa
The guava cottony scale, Capulinia linarosae Kondo & Gullan (Hemiptera: Eriococcidae), is an important pest of guava, Psidium guajava L. (Myrtaceae) in northern Colombia and Venezuela. A species of Metaphycus (Hymenoptera: Encyrtidae) is the only known primary parasitoid associated with this insect pest. The parasitoid is herein described as M. marensis Chirinos & Kondo, sp. nov., based on morphological characteristics of the adult female and male. Biological studies on adult longevity, fecundity, host preference, and sex ratio were conducted. The maximum longevity of the female and the male were 8.0 and 6.5 days, respectively, when fed with diluted honey. On average, a fed mated female laid approximately 40 eggs. Adult females of M. marensis were shown to prefer to parasitize 11- to 15-day-old adult females of C. linarosae and do not parasitize first-instar nymphs of the host eriococcid. The female-to-male sex ratio of the parasitoid was 2.24: 1. When ovipositing females of M. marensis were given only small-sized individuals (second-instar nymphs) of C. linarosae, generally the resulting progeny was a single male wasp. This parasitoid species has arrhenotokous reproduction and is a facultative gregarious parasitoid. These results show a short adult longevity, as well as a relatively low fecundity of the female compared with studies conducted on other Metaphycus species. This study provides essential baseline information for future biological control programmes for C. linarosae .